Model Mitigasi Krisis Literasi Qur’ani di Tengah Fenomena Konten Islami TikTok dengan Pendekatan Superfisial - Fatahillah Arrozi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to formulate a mitigation model for the crisis of Qur’anic literacy amid the rise of superficial Islamic content on TikTok. The research adopts a qualitative descriptive approach with a library research design, analyzing and synthesizing relevant literature from reputable journals, books, and reports published over the last five years. The findings reveal that the popularity of TikTok content, which often prioritizes entertainment and visual appeal over substance, significantly impacts the depth of Qur’anic understanding among Generation Z. Based on the synthesis of the literature, this study proposes a crisis mitigation model using the principles of Islamic education management—planning, organizing, actuating, and controlling (POAC). The proposed model emphasizes digital Qur’anic literacy programs, curated content, and capacity-building initiatives for educators and content creators to produce engaging yet substantive Islamic content. This research contributes to the field of Islamic education by offering a conceptual framework for integrating digital literacy with Qur’anic learning, particularly in addressing the challenges posed by social media. Although limited to conceptual analysis, this study provides practical recommendations for educational institutions, teachers, and digital da’wah practitioners to strengthen Qur’anic literacy among young Muslims.